No Best Way to Build a Mental Model. - Simonelis, Alex (Communications of the ACM, 2008)
A letter to the editor is presented in response to the article "Software Design and the Monkey's Brain," by Robert L. Glass in his "Practical Programmer" column in the June 2008 issue.